A Clinical Case of COVID-19-Associated Pulmonary Aspergillosis (CAPA), Illustrating the Challenges in Diagnosis (Despite Overwhelming Mycological Evidence) - White, P. Lewis; Springer, Jan; Wise, Matt P.; Einsele, Hermann; Loeffler, Claudia; Seif, Michelle; Prommersberger, Sabrina; Backx, Matthijs; Loffler, Jurgen (Journal of Fungi, 2022)
The COVID-19 pandemic has resulted in large numbers of patients requiring critical care management. With the established association between severe respiratory virus infection and invasive pulmonary aspergillosis (7.6% for COVID-19-associated pulmonary aspergillosis (CAPA)), the pandemic places a significant number of patients at potential risk from secondary invasive fungal disease. We described a case of CAPA with substantial supporting mycological evidence, highlighting the need to employ strategic diagnostic algorithms and weighted definitions to improve the accuracy in diagnosing CAPA.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Aspergillus; CAPA; COVID-19; Diagnostics